Comparative analysis of balloon- versus mechanically-expandable transcatheter heart valves considering landing zone calcification. Issue 6 (June 2018) - Schofer, Niklas; Deuschl, Florian; Schön, Gerhard; Seiffert, Moritz; Linder, Matthias; Schaefer, Andreas; Schirmer, Johannes; Lubos, Edith; Reichenspurner, Hermann; Blankenberg, Stefan; Conradi, Lenard; Schäfer, Ulrich
Abstract: Background: The balloon-expandable Sapien 3 (Edwards Lifesciences, Irvine, CA, USA) and the mechanically-expandable Lotus valve (Boston Scientific, Marlborough, MA, USA) are established devices for transcatheter aortic valve implantation. We sought to compare both transcatheter heart valves (THV) under consideration of the extent of THV landing zone calcification. Methods: This retrospective analysis includes consecutive patients with severe aortic stenosis treated with Sapien 3 (S3; n = 212) or Lotus ( n = 61) THV via transfemoral access. Outcome was assessed according to VARC II definitions. Rate of paravalvular leakage (PVL), periprocedural stroke, and permanent pacemaker implantation (PPI) was adjusted for THV landing zone calcification as calculated by multi-slice computed tomography. Results: There was no difference in preoperative risk (all results as follows S3 vs. Lotus: STS-PROM 5.9 ± 5.6% vs. 4.8 ± 2.6%, p = 0.14), rate of device success (95.3% vs. 95.1%, p = 0.67), 30-day mortality (1.9% vs. 4.9%, p = 0.16), periprocedural stroke (1.4% vs. 4.9%, p = 0.27), and major access site complications (9.4% vs. 9.8%, p = 0.93). PPI was more frequent (19.4% vs. 34.4%, p = 0.01) and significant PVL was less frequent (≥mild PVL: 17.6% vs. 3.7%, p = 0.04) after Lotus implantation. No association was found between landing zone calcification and periprocedural stroke rate (OR 1.19, 95%CI 0.92–1.54, p = 0.17) or need for PPI (OR 1.04, 95%CI 0.91–1.18, p = 0.57). The extent of landing zone calcification was associated with risk for PVL ≥mild (OR 1.21, 95%CI 1.03–1.42, p = 0.02). After adjusting for landing zone calcification risk for PVL ≥mild was lower with the Lotus valve (OR 0.15, 95%CI 0.02–0.54, p = 0.01). Conclusion: Both THVs yield comparable procedural and clinical outcomes except for a higher PPI rate with the Lotus valve, which is independent from the extent of landing zone calcification. The extent of landing zone calcification is associated with an increased risk for PVL for both THV, but is significantly reduced with the Lotus valve.